Production and exchange of meaning in instagram beauty influencer visual content in Indonesia: a social semiotic analysis - Ariani Kusumo Wardhani; Hanisa Hassan; Irfandi Musnur (Gelar : Jurnal Seni Budaya, 2023)
The development of technology aligns with the evolution of information media, which is increasingly dynamic in contemporary times. Instagram serves as a social media platform employed by beauty influencers to disseminate information pertaining to beauty. Visual content showcasing diverse beauty reviews captivates a substantial female audience, resulting in millions of followers on Instagram. This study aims to interpret the conveyed meanings by Indonesian female beauty influencers, such as Tasya Farasya, Kesha Ratuliu, and Hanggini. The qualitative methodology employs social semiotic theory to extract meanings embedded in the text or discourse presented by each influencer, considering social and cultural perspectives. This research adopts a constructivist paradigm, emphasizing the production and exchange of meanings. The study analyzes the meaning behind the messages conveyed by each beauty influencer on social media. The images portrayed by Tasya Farasya, Kesha Ratuliu, and Hanggini exhibit distinct representations both interactively and compositionally. The interactive metaphoric function is evident in the endurance of their image, showcased through visually appealing content on Instagram photos. This results in the creation of a multimodal visual composition in the photos.